A clinical review of using a high-flow nasal cannula for patients with COVID-19 infection - Mutia Ayu Pratiwi; Abi Muhlisin (Journal of Holistic Nursing Science, 2022)
Coronavirus Disease 2019 (COVID-19) is caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV 2). The most common manifestations of COVID-19 include fever > 37.5˚C, cough, flu, anosmia, and respiratory distress—the virus cause Acute Respiratory Distress Syndrome (ARDS), which quickly turns into respiratory failure. Therefore COVID-19 patients with ARDS require intensive care in a hospital with oxygen support. One type of oxygen therapy used to treat COVID-19 with ARDS is a High Flow Nasal Cannula (HFNC) administration. This study aimed to determine the effectiveness of HFNC therapy in COVID-19 patients with ARDS. This study used a literature review research design. Sources of literature were carried out on Google Scholar, Science Direct, Pubmed, and Sage Journal, with the final results obtained from eight reviewed articles. The results of the eight articles stated that using HFNC positively impacted the decreased need for mechanical ventilation and increased gas exchange of COVID-19 patients with ARDS. Keywords: COVID-19; oxygen therapy; nursing care; infectious diseases; prevention strategy